Legal Analysis of the Crime of Aggravated Theft: Assessing Social Justice in Law Enforcement (Case Study of Case Number 1454/Pid.B/2024/PN Sby) - Hidayat, Mahatir Muhammad; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
The Unitary State of the Republic of Indonesia (NKRI) is a state of law. Based on Article 1 paragraph 3 of the 1945 Constitution, it means that Indonesia is a state that is not based on power (maachstaat). All aspects of society, statehood, and government must be regulated by law. To realize a state of law, legal instruments are needed to regulate all aspects of people's lives to maintain justice and balance. Pancasila and the 1945 Constitution as a philosophical basis are used in national and state life, not only in terms of legislation, but also in all aspects of life. The approach method used in this study is the normative legal approach method. In the normative legal approach, legal research is carried out by examining library materials or secondary data as basic materials for research by conducting searches for regulations and literature related to the problems to be studied. The judge in this case applied a penal policy that prioritized sensitivity to the defendant's condition, including his socio-economic background, the losses that had been recovered, and a cooperative attitude during the legal process. This approach reflects the restorative and humanistic spirit that is also the spirit of national criminal law reform according to the thoughts of figures such as Muladi and Barda Nawawi Arief. Within this framework, Muladi emphasized that the criminal justice system should "not only be repressive and retributive, but must also have a rehabilitative and reintegrative dimension." Meanwhile, Barda Nawawi Arief is of the opinion that the Indonesian criminal justice system must take into account the values of justice that exist in society, because "criminal law does not only reflect legalistic values, but also developing moral and social values." This decision shows a progressive trend in criminal justice practices, emphasizing the importance of the function of law as a tool of social engineering that is adaptive to the dynamics of justice and morals in society. Thus, punishment does not merely function as retribution, but as a means of guidance, rehabilitation, and prevention.